PENGARUH WORKING CAPITAL MANAGEMENT (WCM) TERHADAP PROFITABILITAS PERUSAHAAN PERTAMBANGAN (Pada Sektor Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2014-2019) - Wulandari, Cahyani Sulistyaning; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2021)
ABSTRACT This research aimed to analyze the impact of Working Capital Management (WCM) and corporate profitability of Indonesian Mining Firms in the period 2014-2019. Profitability is measured by using Return on Assets (ROA) and Gross Operating Profit (GOP). The independent variabels used in this study are Cash Conversion Cyle (CCC) and Cash Conversion Cycle2 (CCC2 ). Followed by control variables consisting of Firm Size (SIZE), Sales Growth (GROWTH), Firm Age (AGE), Leverage (LEV), and Liquidity (CR). This research also expected to give insight for financial management developments, provide information to managers for making decisions about working capital policies, and used as reference for further research. The sample used in this study collected from 33 mining firms that have been listed on the Bursa Efek Indonesia (BEI) with complete data needed to calculate the variables on the period 2014-2019. The analysis technique in this study is using the GMM model specifications, the Wald test, and the t statistical test using panel regression models. Through the Wald test shows that CCC, CCC2 , SIZE, GROWTH, AGE, LEV, and CR have significant effect on the ROA of mining firms. The results of the t-test in this study indicate that CCC and ROA is U-shaped. Furthermore, variabel AGE, CR, GROWTH, has a positive and significant effect on ROA. Variable control LEV has a negative and significant on ROA. Variable control SIZE and CR has a positive and insignificant on ROA. Through the Wald test shows that CCC, CCC2 , SIZE, GROWTH, AGE, LEV, and CR have significant effect on the GOP of mining firms. The results of the t-test in this study indicate that CCC and GOP is U-shaped. Furthermore, variabel CR, GROWTH, and LEV has a positive and significant effect on GOP. Variable control SIZE has a negative and significant on GOP. Variable control AGE has a positive and insignificant on ROA.